2020
DOI: 10.1016/j.medmal.2020.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab therapy reduced intensive care unit admissions and/or mortality in COVID-19 patients

Abstract: Introduction.-No therapy has yet proven effective in COVID-19. Tocilizumab (TCZ) in patients with severe COVID-19 could be an effective treatment. Method.-We conducted a retrospective case-control study in the Nord Franche-Comté Hospital, France. We compared the outcome of patients treated with TCZ and patients without TCZ considering a combined primary endpoint: death and/or ICU admissions. Results.-Patients with TCZ (n = 20) had a higher Charlson comorbidity index (5.3 [±2.4] vs 3.4 [±2.6], P = 0.014), prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
224
1
14

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(252 citation statements)
references
References 19 publications
13
224
1
14
Order By: Relevance
“…Thus, 28 articles included 991 COVID-19 patients underwent tocilizumab administration were included in this study 10,11, . Of the 28 included studies, 7 of which included 377 patients were case-control studies with a control group not using tocilizumab 28,29,32,36,39,40,42 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, 28 articles included 991 COVID-19 patients underwent tocilizumab administration were included in this study 10,11, . Of the 28 included studies, 7 of which included 377 patients were case-control studies with a control group not using tocilizumab 28,29,32,36,39,40,42 .…”
Section: Resultsmentioning
confidence: 99%
“…Data were unavailable for mortality in 3 studies, and a pooled all-cause death rate of 16% (95% CI, 11-22%; I 2 = 67%, P< 0.0001) was reported in 870 patients when treated with tocilizumab. 17 studies 10,11,19,[21][22][23][25][26][27][28][29]31,33,[35][36][37]40 comprising 562 patients were de ned as severe COVID-19 infection, and the pooled ORR of treatment with tocilizumab was 78% (95% CI, 70-85%; I 2 = 65%, P< 0.0001), while pooled ORR in 64 nonsevere infection was 93% (95% CI, 85-98%; I 2 = 0%, P=0.66) ( Figure S2).…”
Section: Impact Of Tocilizumab Treatment On Orr and Mortality Of Covimentioning
confidence: 99%
See 1 more Smart Citation
“…Rheumatologists are on the very frontline in the management of COVID-19, although very few musculoskeletal disorders have been reported (7). The use of hydroxychloroquine for treating based on the antiviral activity of chloroquine (9)(10) and above all that of Tocilizumab (TCZ) (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), a humanized anti-IL-6 receptor antibody widely used in the treatment of rheumatoid arthritis and juvenile idiopathic arthritis, has put rheumatologists in the spotlight (21,22). Yet TCZ, like other biological Disease Modifying Anti-Rheumatic Drugs (bDMARDs), has been classi ed as a potentially immunosuppressive drug due to the increased risk of severe infection in patients treated with bDMARDs (23).…”
Section: Introductionmentioning
confidence: 99%
“…However, e cacy of tocilizumab in COVID-19 disease, has yet to be demonstrated. To date no results from randomized clinical trials testing tocilizumab have been reported and, the few observational studies which has a comparative group, report con ictive results on mortality or clinical improvement (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%